ANALISIS YURIDIS TENTANG TUGAS DAN FUNGSI KOMISI KEJAKSAAN DALAM MEWUJUDKAN LEMBAGA KEJAKSAAN REPUBLIK INDONESIA YANG PROFESIONAL - Ludy Himawan; Alvi Syahrin; Suhaidi Suhaidi; Marlina Marlina (Universitas Sumatera Utara, 2018)
ABSTRACT The system of supervision in the criminal justice system has two forms, i.e. built in control and supervision of the institution. Supervision supervisory control is built in which is performed inside the institution, while the institution of supervision conducted by supervisors outside the institution. Every law enforcement agency has a supervisory institution each, judge District Court overseen by judge high, high judge supervised by the Supreme Court and others. In addition, outside of the institution, each institution supervised by the judicial Commission, the independent agency overseeing the performance of judges, the State Attorney Commission overseeing the performance of prosecutors and others. The built in control in the supervision of the criminal justice system is not only overseeing the performance of law enforcement officials in each agency, but also supervise the process in law enforcement. The performance of the District Court will be overseen by the High Court and the High Court will be supervised by the Supreme Court. The verdict by the District Court will be judged by a court to have a position on it, in this case the High Court and so on. So is the State agency that is supervised by the Prosecutor and the Attorney General's Office. The establishment of the Commission as an institution external supervisory Prosecutor Prosecutor's Office was formed in order to improve the quality and performance of the institutions of the State Attorney. The performance of the prosecution agencies assessed the community not optimal the Foundation of this institution so that in Act No. 16 of 2004 about Attorney General RI in section 38 allows the existence of a Commission which aims to improve the quality and performance of the institutions of the State Attorney. As a follow-up of the Article then the President issued Presidential Regulation No. 18 in 2011 about the State Attorney Commission as an umbrella law duties and wewenangnnya. But in this regulation is not set explicitly how the mechanism monitoring and execution of the authority of the State Attorney Commission. In addition in the execution of the duties and authority of the Commission Attorney experienced barriers. How the State Attorney Commission overcome barriers and maximize the authority given to achieve the establishment of this institution. Keywords : External supervisory Attorney, the State Attorney's duties and Functions of the Commission.